2018
DOI: 10.1016/j.physleta.2017.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Pair interactions of heavy vortices in quantum fluids

Abstract: The dynamics of quantum vortex pairs carrying heavy doping matter trapped inside their cores is studied. The nonlinear classical matter field formalism is used to build a universal mathematical model of a heavy vortex applicable to different types of quantum mixtures. It is shown how the usual vortex dynamics typical for undoped pairs qualitatively changes when heavy dopants are used: heavy vortices with opposite topological charges (chiralities) attract each other, while vortices with the same charge are repe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It is demonstrated that exciton-polaritons may condense at room temperatures forming a nonlinear superfluid medium [102]. Along with other types of quantum fluids, exciton-polariton condensates support many exotic excitations, including solitons and quantum vortices [103][104][105][106]. Regarding possible applications, it is already suggested theoretically and is demonstrated experimentally that nonlinear properties of exciton-polariton condensates can be implemented to create quantum simulators [107], capable of solving optimization problems with a large number of degrees of freedom.…”
Section: More Quasiparticlesmentioning
confidence: 99%
“…It is demonstrated that exciton-polaritons may condense at room temperatures forming a nonlinear superfluid medium [102]. Along with other types of quantum fluids, exciton-polariton condensates support many exotic excitations, including solitons and quantum vortices [103][104][105][106]. Regarding possible applications, it is already suggested theoretically and is demonstrated experimentally that nonlinear properties of exciton-polariton condensates can be implemented to create quantum simulators [107], capable of solving optimization problems with a large number of degrees of freedom.…”
Section: More Quasiparticlesmentioning
confidence: 99%
“…Such composite objects are referred as doped vortices. Their properties are investigated in the regimes where the doping mass becomes close to the total mass of superfluid particles forming a vortex [8,9]. Such formations are dynamically stable and, possessing both vorticity and enhanced inertia, demonstrate properties which are different from the pure vortex case.…”
Section: Dynamics Of Vortex Pairs Doped With Heavy Bosonic Mattermentioning
confidence: 99%
“…For example, exotic fundamental properties of exciton-polaritons allow to exceed limitations of classical photonics [6]. As it was shown, the exciton-polaritons may form condensates at room temperatures and demonstrate nonlinear coherent behavior typical for quantum fluids [7][8][9][10]. Some applications of their properties in polariton simulators and potential exciton-polariton integrated circuits have been discussed recently [11][12][13].…”
Section: Introductionmentioning
confidence: 99%